Knowing who we teach: Tracking attitudes and expectations of first‐year postsecondary language learners. (17th February 2021) - Knouse, Stephanie M.; Bessy, Marianne; Longest, Kyle C.
Abstract: Given waning second language (L2) enrollments in K‐16 contexts, L2 programs must strive to understand their learners, as changes in their sociocultural environment can impact students' attitudes and, subsequently, their desire and ability to learn an L2. Thus, the authors conducted a two‐wave analysis of 68 first‐year L2 students' attitudes, dispositions, and expectations of L2 learning. Findings show that, as a group, first‐year students entered the postsecondary arena with positive dispositions. Analyzing students' traits and prior L2 experiences was a more illustrative way of predicting how their opinions evolved. Specifically, female gender, lack of pre‐high school L2 instruction, lack of travel experience in a country where the L2 is spoken, and enrollment in a 100‐level course were all found to negatively shape these attitudes over time. The authors contend that L2 programs should regularly analyze learners' dispositions along with their traits to better engage and retain first‐year postsecondary L2 students. The Challenge: Why should second language (L2) programs systematically evaluate first‐year postsecondary students' attitudes and expectations toward L2 learning? What learner traits might condition these opinions? How can tracking the development of these self‐reported attitudes and expectations over time assist practitioners in better serving their students?